Integrating riddles as instructional resource in the Competency-Based Curriculum for Early Years Education in Kenya - Mokaya, Gloria Kemunto; Kebaya, Charles (Research Journal in Advanced Humanities, 2022)
The introduction of the Competency-based curriculum in Kenya has had far-reaching changes in the teaching and learning of basic education in Kenya today. Teachers, are for instance, required to adopt innovative methods of content delivery in order to enhance learners’ mastery of the content. Such innovative practices have seen teachers deploy various locally available materials as instructional resources in their classrooms. While riddles have multiple functions to play in society, this paper analyses benefits that learners will obtain in using riddles as instructional resources in Early Years Education in Kenya. Primary data for analysis was obtained from a field study conducted among learners in purposively sampled primary schools in Manga sub-county, Nyamira County. Pre-observation interviews, lesson observation and post-observation interviews were used in data collection. Thus, the authors examine various competency-based skills embedded in riddles such as creative and critical thinking skills, cognitive skills, numeracy skills, collaborative skills, and environmental awareness skills. The article concludes that riddles enhance learners’ competencies and therefore there is need to embrace them as instructional resources in Early Years Education in Kenya.